A novel dipole charge density mapping system integrated in robotics offers advantages for ablation of atrial tachycardias: first-in-human experience. (19th May 2022) - Gagyi, R; Noten, AME; Wijchers, S; Yap, SC; Hoogendijk, M; Szili-Torok, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Catheter ablation (CA) for atrial tachycardia (AT) and atrial flutter (AFL) offers favorable acute and long-term outcomes. Until recently, mapping of AT/AFL was only possible with sequential mapping methods using manually controlled catheters. Even by implementing multielectrode mapping, some limitations exist during mapping of short-lived arrhythmias and ATs with unstable CL. Remote magnetic navigation (RMN) with its atraumatic catheter design has superior safety profile and excellent accuracy. Recently, a novel high-resolution mapping system (AcQMap) can be used in combination with RMN (AcQMap-RMN). Purpose: To assess the feasibility, safety and efficacy of AcQMap-RMN guided ablation in the management of complex ATs. Methods: All patients undergoing CA for AT/AFL using AcQMap-RMN were included. The AcQMap system utilizes two different types of mapping: Single Position Map (SMP) and SuperMap, allowing mapping of both non-sustained and sustained ATs. Procedural efficiency was characterized by procedure time, total ablation time and radiation doses. Acute success was defined by arrhythmia source elimination. Efficacy data are based on 12-month follow up and number of redo procedures. Procedural safety was evaluated by intra- and post-procedural complications. Results: A total number of 76 patients were referred for CA with AT/AFL (mean age 59.0±13.2), including 3 patients with inappropriate sinus tachycardia and 73 patients with AT/AFL. Out of 73 patients, 8 had perinodal AT. From the remaining 65 patients, 38 had de novo, 22 had post-PVI, and 5 patients had post-MAZE AT/AFL. Twenty-nine patients had short-lived ATs and were mapped exclusively by SPM. The mean procedure time was 175.9±61.4 min, mean ablation time 964.0 (IQR 422.0-1693.0) s, and mean radiation dose was 152.0(IQR 86.7-294.0) mGy. Acute success was documented in 70 procedures (92.1%). From de novo AT/AF patients 4 (10.5%), from post-PVI and post-MAZE AT/AFL patients 3 had recurrence at the end of the follow-up period (11.1%). Four patients had redo procedure. Three patients had post-procedural complications including 2 patients with groin hematoma and 1 patient with transient ischemic attack. Conclusion: AcQMap-RMN integration offers improved efficiency, high success and low complication rates in complex AT ablation.